Facile synthesis and emission enhancement in NaLuF4 upconversion nano/micro-crystals via Y3+ doping. Issue 1 (December 2017) - Lin, Hao; Xu, Dekang; Li, Anming; Yao, Lu; Qiu, Zhiren; Yang, Shenghong; Zhang, Yueli
Abstract A series of Y3+ -absent/doped NaLuF4 :Yb3+, Tm3+ nano/micro-crystals were prepared via a hydrothermal process with the assistance of citric acid. Cubic nanospheres, hexagonal microdisks, and hexagonal microprisms can be achieved by simply adjusting the reaction temperature. The effect of Y3+ doping on the morphology and upconversion (UC) emission of the as-prepared samples were systematically investigated. Compared to their Y3+ -free counterpart, the integrated spectral intensities in the range of 445–495 nm from α-, β-, and α/β-mixed NaLuF4 :Yb3+, Tm3+ crystals with 40 mol% Y3+ doping are increased by 9.7, 4.4, and 24.3 times, respectively; red UC luminescence intensities in the range of 630–725 nm are enhanced by 4.6, 2.4, and 24.9 times, respectively. It is proposed that the increased UC emission intensity is mainly ascribed to the deformation of crystal lattice, due to the electron cloud distortion in host lattice after Y3+ doping. This paper provides a facile route to achieve nano/micro-structures with intense UC luminescence, which may have potential applications in optoelectronic devices.